2018
DOI: 10.1098/rspb.2018.0264
|View full text |Cite
|
Sign up to set email alerts
|

Isolation by environment in the highly mobile olive ridley turtle (Lepidochelys olivacea) in the eastern Pacific

Abstract: Spatial and temporal scales at which processes modulate genetic diversity over the landscape are usually overlooked, impacting the design of conservation management practices for widely distributed species. We examine processes shaping population divergence in highly mobile species by re-assessing the case of panmixia in the iconic olive ridley turtle from the eastern Pacific. We implemented a biophysical model of connectivity and a seascape genetic analysis based on nuclear DNA variation of 634 samples collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 56 publications
1
26
2
Order By: Relevance
“… Full sites include two‐letter country codes. Also indicated is whether site was originally included in the Rodríguez‐Zárate et al (2018; R‐Z) data or present study (P), and population inferred by Rodríguez‐Zárate et al (2018) …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… Full sites include two‐letter country codes. Also indicated is whether site was originally included in the Rodríguez‐Zárate et al (2018; R‐Z) data or present study (P), and population inferred by Rodríguez‐Zárate et al (2018) …”
Section: Introductionmentioning
confidence: 99%
“…Though comprehensive, the study did not survey genetic variability of key population index sites in Costa Rica (but did survey index sites in Mexico and Nicaragua, Table 1; Abreu‐Grobois & Plotkin, 2008; Bernardo & Plotkin, 2007). It is difficult to test for this Mexican–Central American split using mtCR haplotypes because haplotypes are not well reported for Central America, and the MUs (Mexican and Central American populations) proposed by Rodríguez‐Zárate et al (2018) based on nuclear genetic variability are yet to be formally integrated into management frameworks. Further, while Rodríguez‐Zárate et al (2018) found that environmental variables (namely oceanographic features such as the Costa Rica Dome) may play a role in this structuring, other factors such as relatedness and the effects of bottleneck events were not explored (although they were previously reported for the Mexican population; Rodríguez‐Zárate, Rocha‐Olivares, & Beheregaray, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, local adaptation can evolve in the presence of gene flow, and even sometimes, gene flow may promote local adaptation through the introduction of genetic variation, the spread of advantageous alleles, nonrandom dispersal, and demographic benefits (Räsänen & Hendry, 2008). In the last few years, there has been a growing interest in understanding how gene flow and divergent selection interact to generate spatial pattern of genetic variation in heterogeneous habitats (Ferchaud & Hansen, 2016;Stanton, Galen, & Shore, 1997;Tigano & Friesen, 2016), and more recently in the marine environment (Diopere et al, 2018;Rodríguez-Zárate et al, 2018;Sexton et al, 2014). A central challenge has been presented to disentangle the relative contributions of selective and neutral processes (such as gene flow and genetic drift) underlying genetic variation (McCairns & Bernatchez, 2008;Räsänen & Hendry, 2008;Sexton et al, 2014;Tigano & Friesen, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, few studies have addressed spatial variation of outlier loci among populations and how these might contribute towards shaping population divergence in natural systems. In addition, it can be challenging to disentangle the signatures of potential adaptation to different environments from the simple isolating effect of distance, especially as a high degree of collinearity exists between environmental gradients and neutral population structure (Wang & Bradburd 2014;Manthey & Moyle 2015;Prunier et al 2017;Weber et al 2017;Rodríguez-Zárate et al 2018). In broad spatial and environmental contexts, both Isolation By Distance (IBD) and Isolation By Environmental (IBE) will act in differentiating populations.…”
Section: Introductionmentioning
confidence: 99%